Early risk stratification of patients with suspected chronic mesenteric ischaemia using a symptom and mesenteric artery calcium score based score chart - Terlouw, Luke G. (United European Gastroenterol J, 2021)
BACKGROUND: The mesenteric artery calcium score (MACS) identifies patients with possible chronic mesenteric ischaemia (CMI) using standard computed tomography (CT) imaging. The MACS does not necessitate a dedicated computed tomography angiography (CTA) which is required for evaluation of mesenteric artery patency. This study aimed to test the use of a symptom and MACS based score chart to facilitate the selection of patients with a low probability of CMI, in whom further diagnostic workup can be omitted, and to validate the CTA‐based score chart proposed by van Dijk et al. which guides treatment decisions in patients with suspected CMI. METHODS: This retrospective study included consecutive patients with suspected CMI. The Agatston definition was used to calculate the MACS. Multivariable logistic regression analysis was used to create a MACS score chart, which was applied in all patients to determine its discriminative ability. The score chart by van Dijk et al. was validated in this independent external patient series. RESULTS: Hundred‐ninety‐two patients were included, of whom 49 had CMI. The MACS score chart composed of the variables weight loss, postprandial abdominal pain, history of cardiovascular disease, and MACS, showed an excellent discriminative ability (area under the curve [AUC] 0.87). CMI risks were 2.1% in the low‐risk group (0–4 points) and 39.1% in the increased risk group (5–10 points); sensitivity (97.8%) and negative predictive value (NPV; 97.9%) were high. The CTA‐based score chart by van Dijk et al. showed an excellent discriminative ability (AUC 0.89). CONCLUSION: The MACS score chart shows promise for early risk stratification of patients with suspected CMI based on a near‐perfect NPV. It is complementary to the CTA‐based score chart by van Dijk et al., which showed excellent external validity and is well suited to guide subsequent (invasive) treatment decisions in patients with suspected CMI.